Assessment of Structural and Functional Status in High-rise Building in Tangail Pourashava (Journal of Environmental Science and Natural Resources, 2017)
Today, most of the cities in the world encounter the phenomenon of high rise building. The growth of high rise building in Tangail pourashava has been considerably increased since the last few years. Though high-rise buildings helped in solving the problem of shortage of land and housing, it also caused many problems in different environmental, structural, spatial, functional, socio-economical, and demographic aspects of the city. Our study was to identify the location of high-rise buildings, to classify these buildings by their uses and to investigate the Structural and functional characteristics of high-rise buildings in Tangail Pourashava. For the study both primary and secondary data were collected, primary data has been collected from field survey and secondary data has been collected from different journals and published and unpublished publications. The study also focused on the existing high-rise buildings safety and security system available in those buildings and made recommendation that the buildings should follow the Bangladesh National Building Code (BNBC) guidance strictly to ensure all safety aspects.J. Environ. Sci. & Natural Resources, 10(1): 125-132 2017